2013
DOI: 10.1002/hep.26185
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal albumin dialysis with the molecular adsorbent recirculating system in acute-on-chronic liver failure: The RELIEF trial

Abstract: on behalf of the RELIEF study group Acute-on-chronic liver failure (ACLF) is a frequent cause of death in cirrhosis. Albumin dialysis with the molecular adsorbent recirculating system (MARS) decreases retained substances and improves hemodynamics and hepatic encephalopathy (HE). However, its survival impact is unknown. In all, 189 patients with ACLF were randomized either to MARS (n 5 95) or to standard therapy (SMT) (n 5 94). Ten patients (five per group) were excluded due to protocol violations. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
361
1
19

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 492 publications
(393 citation statements)
references
References 33 publications
12
361
1
19
Order By: Relevance
“…[26,38] However, the albumin loss during Prometheus-therapy can reach 3 g/L (P = 0.055). [31,39] We observed no significant negative dynamics of serum albumin [oscillations: 32 (30-35) and 30 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35) g/L, P = 0.052, before and after MARS-therapy; 33 (31-34) and 31 (28-36) g/L, P = 0.051, before and after Prometheus-therapy], which is probably due to the adequate routine correction of hypoproteinemia in patients with ALF. [39] Likewise, despite published data on the loss of coagulation factors during Prometheus-therapy, [40] we did not observe clinically significant hemorrhagic complications.…”
Section: Extracorporeal Blood Purification In Intensive Care Patientsmentioning
confidence: 84%
See 1 more Smart Citation
“…[26,38] However, the albumin loss during Prometheus-therapy can reach 3 g/L (P = 0.055). [31,39] We observed no significant negative dynamics of serum albumin [oscillations: 32 (30-35) and 30 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35) g/L, P = 0.052, before and after MARS-therapy; 33 (31-34) and 31 (28-36) g/L, P = 0.051, before and after Prometheus-therapy], which is probably due to the adequate routine correction of hypoproteinemia in patients with ALF. [39] Likewise, despite published data on the loss of coagulation factors during Prometheus-therapy, [40] we did not observe clinically significant hemorrhagic complications.…”
Section: Extracorporeal Blood Purification In Intensive Care Patientsmentioning
confidence: 84%
“…[29] The beneficial effect of these procedures on clinical and laboratory parameters is explained by the removal of vasoactive substances and toxins, leading to improvements in organ and tissue perfusion, hemodynamic parameters and kidney function and reducing portal hypertension, intracranial pressure and hepatic encephalopathy. [30,31] The experience from implementing this therapy in adults allows the use of extracorporeal liver support to be recommended in pediatric practice. [32][33][34] MARS-therapy is a method of albumin dialysis that uses a filter permeable to substances with a molecular weight of up to 50 kDa.…”
Section: Extracorporeal Blood Purification In Intensive Care Patientsmentioning
confidence: 99%
“…Despite potentially positive effects on clinical and laboratory parameters, no study has been able to demonstrate a significant survival benefit in ALF15 or ACLF patients 14. A systematic evaluation of MARS has not been undertaken with respect to PHLF.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the Molecular Adsorbent Recirculating System (MARS) has emerged as a promising tool due to its capacity to remove water‐soluble and albumin‐bound toxins and to improve several clinically relevant hemodynamic and biochemical parameters in patients suffering from ALF or ACLF 9, 10, 11, 12, 13. Large, randomized, controlled trials did, however, fail to demonstrate a statistically significant survival benefit 14, 15. In the PHLF situation, only a few single‐center experiences have addressed the use of MARS as a rescue treatment option,16, 17, 18, 19, 20 and all of them suffer from heterogeneous patient groups and a lack of standardized treatment protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular absorbent recirculating system (MARS) removes albumin-bound and water-soluble substances, including NO and TNF, which are involved in pathogenesis of HRS. MARS has been shown to improve neurological function and coagulation parameters although a randomised trial of 189 patients reported no beneficial effect on survival of MARS therapy in patients with acute or chronic liver failure (23).…”
Section: Extracorporeal Support Systemsmentioning
confidence: 99%